Development of an internet of things-based weather station device embedded with O2, CO2, and CO sensor readings - Megantoro, Prisma; Saud Al-Humairi, Safaa Najah; Kustiawan, Arya Dwi; Arsalan, Muhammad Rafi Nabil; Prastio, Rizki Putra; Awalin, Lilik Jamilatul; Vigneshwaran, Pandi (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Weather station devices are used to monitor weather parameter conditions, such as wind direction, speed, rainfall, solar radiation level, temperature, and humidity. This article discusses the design of a customized weather station embedded with gas concentration readings, whereby the gas concentration measurement includes oxygen (O2), carbon dioxide (CO2), and carbon monoxide (CO). The measurements and data processing of input sensors were transmitted to an Arduino Uno microcontroller, and the input data were then remitted to Wemos D1 Mini to be uploaded to a cloud server. Furthermore, the gas sensors' characterization methods were also considered to reveal the obtained results of accuracy, precision, linearity, and hysteresis. An android-based mobile application was also designed for monitoring purposes. The system in our experiment utilized an internet connection with a field station, base station, and database server.